Roles of different molecular weights of dissolved organic matter in arsenic enrichment in groundwater: Evidences from ultrafiltration and EEM-PARAFAC - Li, Xiaomeng; Guo, Huaming; Zheng, Hao; Xiu, Wei; He, Wei; Ding, Qian (Applied geochemistry, 2019)
Molecular weight (MW) is a fundamental property of dissolved organic matter (DOM) that may affect the interaction between DOM and metals/metalloids. However, understanding of MW property of groundwater DOM and its roles in arsenic (As) mobilization needs to be improved. In this study, two surface water samples and 12 groundwater samples with different concentrations of As and dissolved organic carbon (DOC) were taken to evaluate the effects of DOM MW on As mobilization by using sequential ultrafiltration technique under a N2 atmosphere. Concentrations of As, Fe, DOC, and spectroscopic properties of OM in each ultrafiltered sample were analyzed. Variations of As, Fe and DOC concentrations in different ultrafiltration fractions show that Fe colloids mainly exist in large size particles (10 kDa-0.45 μm fractions), while organic colloids are mainly present in middle size particles (5–10 kDa fractions). The positive correlations between As and Fe in 10 kDa-0.45 μm fractions (R2 = 0.76, p < 0.01) and between As and DOC in 5–10 kDa fractions (R2 = 0.61, p < 0.05) indicate that the complexation of As with large-size Fe colloids and middle-size DOM promotes As mobilization. Parallel factor analysis (PARAFAC) of the three-dimensional fluorescence spectra reveals that DOM in all size fractions comprises three major components, namely C1 (terrestrial humic-like component), C2 (microbial humic-like component), and C3 (protein-like component). The positive correlation between C1 (%) and As concentrations (R2 = 0.73, p < 0.05) possibly confirms that terrestrial-derived humic-like substance (HS) should be conducive to As enrichment. The spectroscopic indices of various fractions show that low MW DOM is characterized by more microbe-associated OM. Some samples have more than 90% of As in the ‘truly dissolved’ fractions, suggesting that microbial utilization of labile low MW DOM should lead to the enrichment of As, in addition to complexation reactions. Therefore, both As-Fe-HS complexation and microbial degradation of low MW DOM being related to the reductive dissolution of As-bearing Fe oxide minerals enhance As mobilization and enrichment in groundwater. •Both Fe colloids and organic colloids are present in high As groundwater.•Arsenic complexes with large-size Fe colloids and middle-size organic colloids.•Terrestrial-derived humic-like substances participate in the complexation reaction.•Low molecular weight DOM is characterized by more microbe-associated OM.•Microbial degradation of low molecular weight DOM enhances As enrichment.